Direct photocatalysis of supported metal nanostructures for organic synthesis. (23rd June 2017) - Wu, Xiayan; Jaatinen, Esa; Sarina, Sarina; Zhu, Huai Yong
Abstract: Many organic synthesis systems use thermal catalysis to achieve higher product efficiency, and it is of interest to drive reactions by light irradiation at moderate reaction conditions. Other than semiconductors, recent reports have shown that metal nanostructures can be used as direct photocatalysts to drive chemical reactions. In this review, we summarize recent progress in direct photocatalysis in organic synthesis using plasmonic and non-plasmonic metal nanostructures. It starts with a comprehensive introduction to surface plasmons and the role of interband transitions in non-plasmonic metal nanostructures. The application of metal nanostructures in organic synthesis is systematically reviewed, followed by the reaction mechanisms; the role of light-excited energetic electrons, enhanced electromagnetic fields and the photothermal effect are detailed. The influence of light intensity and wavelength is discussed, as well as the critical parameters of photocatalyst design. Finally, the outlook and future opportunities of this new exciting field will be discussed.